Peran Audit Internal dalam mencegah fraud di tengah wabah covid-19 (Study Empiris RSUD Dr. Soetomo Surabaya) - Syarifah hatijah; Indrawati Yuhertiana (Jurnal Proaksi, 2021)
This study describes the role of internal auditors in preventing fraud against budget execution in the midst of the covid-19 pandemic. This study aims to obtain empirical evidence regarding the role of the internal supervisory unit as an internal audit in hospitals in preventing fraud in the midst of the covid-19 outbreak (A Study at Dr. Soetomo Hospital Surabaya)". This study uses a qualitative method with a case study approach. at the Internal Supervisory Unit of RSUD Dr. Soetomo Surabaya through data analysis techniques, interviews and documentation. The role of internal audit in hospitals (SPI) was analyzed descriptively with data reduction, narrative presentation, and drawing conclusions on the fraud detection capability inherent in the internal auditor function of the SPI RSUD Dr. Soetomo. This study concluded that the SPI RSUD Dr. Soetomo has carried out the role of fraud prevention by carrying out its duties and functions as stated in the annual supervisory work program including routine supervision, special supervision related to the BTT, Functional and CSR budgets, follow-up monitoring, audit assistance by external auditors and sponsorship licensing control. Internal Auditor of SPI RSUD Dr. Soetomo must improve his competence so that he can detect fraud optimally in monitoring the effectiveness and efficiency of BLU activities, reliability and integrity of financial information and BLUD performance, security of BLUD assets, so as to detect fraud early. Keywords: audit internal, pencegahan fraud, Pandemi covid-19, SPI.